1968
DOI: 10.1063/1.1656022
|View full text |Cite
|
Sign up to set email alerts
|

The Poole-Frenkel Effect with Compensation Present

Abstract: This extended Poole-Frenkel model includes the effects of compensation. The relative densities of donor and acceptor sites control the slope of the log J vs E1/2 plots. With only one type of site present, the slope equals that expected for Schottky emission [slope= (e3/πεε0)1/2/2kT]. When sites of the opposite type compensate, the slope doubles. The degree of compensation must be known to determine the barrier heights separating the emission site from the band edge. Data from metal-silicon nitride-metal device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
190
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(200 citation statements)
references
References 21 publications
9
190
0
1
Order By: Relevance
“…33 Considering the magnitude of the applied electric fields in the a-IGZO thin-film patches and the temperature dependence of the electrical conductance (Figures 3e and f), the conduction mechanisms based on tunneling can be neglected. 33 The P-F conduction is given as: 35,36 I PÀF pEexp 1…”
Section: Resultsmentioning
confidence: 99%
“…33 Considering the magnitude of the applied electric fields in the a-IGZO thin-film patches and the temperature dependence of the electrical conductance (Figures 3e and f), the conduction mechanisms based on tunneling can be neglected. 33 The P-F conduction is given as: 35,36 I PÀF pEexp 1…”
Section: Resultsmentioning
confidence: 99%
“…The plot shows a linear behavior with appreciable deviation from linearity at lower electric field and at higher temperatures of 360 and 380 K. This is attributed to accumulation of space charge at the electrodes [18]. These data can be fitted to the relation [19]:…”
Section: I-v Characteristicsmentioning
confidence: 99%
“…r is a degree of compensation whose value changes between 1 and 2 (1 ≤ r ≤ 2) [20,21], and it defines the effect of trapping or acceptor sensors. When r is equal to 1, then it is named as normal PF, while it corresponds to modified Poole-Frenkel effect or Poole-Frenkel with compensation when r = 2.…”
Section: Conduction Mechanismsmentioning
confidence: 99%
“…However, the analysis have strongly indicated that the conduction mechanism through the laser grown Ta 2 O 5 films in the applied voltage ranges is governed by the PF in the samples having a barrier height separating the traps from the conduction band. PF is based on the emission of trapped electrons toward the conduction band of the insulator [20,21]. Current density governed by the PF mechanism through the dielectric is given as [22];…”
Section: Conduction Mechanismsmentioning
confidence: 99%